Irregular screening participation increases advanced stage breast cancer at diagnosis: A population-based study. (October 2022) - Ding, L.; Greuter, M.J.W.; Truyen, I.; Goossens, M.; De Schutter, H.; de Bock, G.H.; Van Hal, G.
Abstract: Objective: To evaluate the effect of irregular screening behaviour on the risk of advanced stage breast cancer at diagnosis in Flanders. Methods: All women aged 50–69 who were invited to the organized breast cancer screening and diagnosed with breast cancer before age 72 from 2001 to 2018 were included. All prevalent screen and interval cancers within 2 years of a prevalent screen were excluded. Screening behaviour was categorized based on the number of invitations and performed screenings. Four groups were defined: regular, irregular, only-once, and never attenders. Advanced stage cancer was defined as a stage III + breast cancer. The association between screening regularity and breast cancer stage at diagnosis was evaluated in multivariable logistic regression models, taking age of diagnosis and socio-economic status into account. Results: In total 13.5% of the 38, 005 breast cancer cases were diagnosed at the advanced stage. Compared to the regular attenders, the risk of advanced stage breast cancer for the irregular attenders, women who participated only-once, and never attenders was significantly higher with ORadjusted :1.17 (95%CI:1.06–1.29) and ORadjusted :2.18 (95%CI:1.94–2.45), and ORadjusted :5.95 (95%CI:5.33–6.65), respectively. Conclusions: In our study, never attenders were nearly six times more likely to be diagnosed with advanced stage breast cancer than regular attenders, which was much higher than the estimates published thus far. An explanation for this is that the ever screened women is a heterogeneous group regarding the participation profiles which also includes irregular and only-once attenders. The benefit of regular screening should be informed to all women invited for screening. Highlights: Irregular screening significantly increases the risk of advanced stage breast cancer at diagnosis. Never attenders were six times more likely to be diagnosed with advanced stage breast cancer than regular attenders. Women should be encouraged to participate in screening regularly.